The Sanitation Cityscape – Toward a Conceptual Framework for Integrated and Citywide Urban Sanitation - Scott, Pippa; Cotton, Andrew P. (Frontiers in Environmental Science, 2020)
In the last decade, the sanitation service chain model has become the de facto framework for urban non-networked sanitation. People, urban ways of living and the conditions that underpin sustainable services, are too often overlooked in current conceptualizations of urban sanitation service delivery. As the sector moves towards a new paradigm of Citywide Inclusive Urban Sanitation, we suggest it is timely to revisit the conceptual framing of urban sanitation. The Sanitation Cityscape is a conceptual framework for citywide urban sanitation. It identifies the key factors of urban sanitation and locates those using three conceptual environments: The Living Environment, the Service Delivery Environment, and the Enabling Environment. Using a proposed set of 16 indicators and locating existing tools the framework looks beyond the linear framing of sanitation services to gain a better understanding of the surrounding context and externalities. For the researcher and practitioner alike, we suggest that the Sanitation Cityscape can provide a coherent ‘frame’ to locate the components of the urban sanitation puzzle predictably and systematically. It lends itself to rapid diagnostic analysis and more appropriate targeting of appropriate sanitation interventions. The paper includes insights from application of the Sanitation Cityscape framework including an outcome-based sanitation service delivery model; efficiencies in data collection; creating area typologies to align sanitation responses; setting enabling environment analyses boundaries purposefully and intentionally and identifying key interfaces as potential intervention points or system levers. We hope that the Sanitation Cityscape might provide greater consistency and a common vocabulary for urban sanitation.